Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen (Studi Kasus di Butik Ipah Modis Kota Banda Aceh) - Eva Rahmadiani; Faridah Yahya; Musfiana Musfiana (Jurnal Ilmiah Mahasiswa Pendidikan Ekonomi, 2019)
Quality of service has a close relationship with customer satisfaction. Quality provides an impetus to consumers to forge strong bonds with the company. In the long term, such ties allow the company to understand carefully the expectations of consumers and their needs. Services aimed at obtaining customer satisfaction are not easy to do, often also found problems in managing the services of a company and unsuccessful in satisfying most of their customers. Therefore it is necessary to improve the quality of service in order to provide satisfaction to customers. As for the formulation of this research problem is the quality of service, the level of customer satisfaction and the influence of service quality on customer satisfaction at Ipah Modik Boutique Banda Aceh. This research uses quantitative approach. The population in this study were consumers at Ipah Modis Boutique Banda Aceh, while the samples numbered 25 consumers of Ipah Modis Banda Aceh Banders who characterized never make more than one purchase that happened to meet the researcher (incidental sample) .The techniques used in data collection is library research , Field research in the form of documentation and questionnaires. The data analysis technique used multiple linear analysis method. The research result shows that the quality of service provided by Ipah Modis Boutique Banda Aceh in general is good, 63% of respondents answered very well and 37% answered well. Level of satisfaction of consumers Ipah Modis Banda Aceh is very good, the respondents are more dominant to choose alternative answers SP (Very Satisfied) as much as 64% and followed by alternative answers P (Puas) that is as much as 36%. Overall there is the influence of service quality Ipah Modis Banda Aceh to positive customer satisfaction, due to the provision of quality services, then it will create satisfaction in the consumer.